2014
DOI: 10.1371/journal.pone.0111937
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Deficiency and Excess Coexist in China and Induce Thyroid Dysfunction and Disease: A Cross-Sectional Study

Abstract: BackgroundIn spite of the salt iodization, iodine deficiency disorders (IDD) have not been sustainably eliminated in China. There are coastal areas with low iodized salt coverage rates (iodine nutrition is inadequate) and other areas with excessive amounts of iodine in the drinking water.ObjectiveThis study aimed to clarify the association of iodine deficiencies resulting from a low coverage rate of iodized salt, excess iodine intake from drinking water with thyroid function and disease in adults.DesignA cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 35 publications
(39 reference statements)
5
55
1
10
Order By: Relevance
“…These disorders are collectively described as iodine deficiency disorders (IDD) [4,8]. It is also evident that the relationship between iodine intake and the risk of thyroid disease is U-shaped, with both low and high iodine intakes associated with thyroid disease [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These disorders are collectively described as iodine deficiency disorders (IDD) [4,8]. It is also evident that the relationship between iodine intake and the risk of thyroid disease is U-shaped, with both low and high iodine intakes associated with thyroid disease [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of thyroid carcinoma occurs in coastal areas, previous studies have clearly indicated that both Iodine deficiency and iodine excess have impact on the tumorigenesis and progress of TC [25-27], and the mechanisms underlying these two conditions are different for TC. Iodine deficiency inducing thyroid disorders has been clearly defined [28].…”
Section: Discussionmentioning
confidence: 99%
“…22) Of these regions, significant regional differences in subjects with overt hypothyroidism were found, with 2.56% variation in excessive iodine intake, p<0.001), but a correlation between iodine intake and hypothyroidism was not found. 24) In Korea, the frequency of subclinical hypothyroidism in preterm infants born at 34 weeks of gestation or less was higher with high iodine intake from breast milk than with low iodine intake from breast milk both 3 weeks (p=0.033) and 6 weeks (p=0.032) after birth.…”
Section: )mentioning
confidence: 95%